Microstructural modification of pure Mg for improving mechanical and biocorrosion properties. (August 2016) - Ahmadkhaniha, D.; Järvenpää, A.; Jaskari, M.; Sohi, M. Heydarzadeh; Zarei-Hanzaki, A.; Fedel, M.; Deflorian, F.; Karjalainen, L.P.
Abstract: In this study, the effect of microstructural modification on mechanical properties and biocorrosion resistance of pure Mg was investigated for tailoring a load-bearing orthopedic biodegradable implant material. This was performed utilizing the friction stir processing (FSP) in 1–3 passes to refine the grain size. Microstructure was examined in an optical microscope and scanning electron microscope with an electron backscatter diffraction unit. X-ray diffraction method was used to identify the texture. Mechanical properties were measured by microhardness and tensile testing. Electrochemical impedance spectroscopy was applied to evaluate corrosion behavior. The results indicate that even applying a single pass of FSP refined the grain size significantly. Increasing the number of FSP passes further refined the structure, increased the mechanical strength and intensified the dominating basal texture. The best combination of mechanical properties and corrosion resistance were achieved after three FSP passes. In this case, the yield strength was about six times higher than that of the as-cast Mg and the corrosion resistance was also improved compared to that in the as-cast condition.